The Effect of Auditor Quality and Remote Audit on Audit Quality in Indonesia: Moderating Role of Information Technology - Arumega Zaferar; Razana Juhaida Johari; Atika Zarefar; M. Rasuli (Jurnal Dinamika Akuntansi)
Purpose: This study aims to analyze the effect of audit quality and remote audit on audit quality.  In addition, this study will also consider the moderating effect of information technology on the effect of auditor quality and remote audit on audit quality.